Leadership and service delivery in times of change - Sulaiman Olusegun Atiku; Collen Mulife Kurana; Idris Olayiwola Ganiyu (Administrative Sciences, 2023)
There has been a growing concern for excellent service delivery in the public sector. The challenges that are hindering service delivery in Town Councils have been attributed to political interference in appointments and ineffective leadership. The residents in the Town Council have been experiencing power outages and water shortages. The livelihoods of the residents and business operations have been hindered by these difficulties. This study investigates the influence of leadership on service delivery in a Town Council in Namibia. A qualitative research approach was adopted to analyse the influence of leadership practices on service delivery in times of change. A total of ten participants were sampled from a population of 117 staff members using a purposive sampling. Face-to-face interviews were conducted using a semi-structured interview guide. Participants views were tape recorded, transcribed into Microsoft Word, and analysed using thematic analysis via NVivo 12. The results showed that logistical difficulties, political interference, lack of human resources, and financial constraints, are the challenges hampering service delivery in the Town Council. The need for managers and supervisors to inspire, coach, mentor, and motivate their subordinates to enhance service delivery using a transformational leadership style is evident in the results. Therefore, the Town Council should prioritise budgeting, foster public-private partnerships, promote innovation, and ensure stakeholder engagement to enhance service delivery in the Town Council.
Keywords: 350; leadership practices; Namibia; public sector; service delivery; stakeholders' engagement; Town Council; transformational leadership